Comorbidities and the risk of mortality in patients with bronchiectasis: an international multicentre cohort study. Issue 12 (December 2016) - McDonnell, Melissa J; Aliberti, Stefano; Goeminne, Pieter C; Restrepo, Marcos I; Finch, Simon; Pesci, Alberto; Dupont, Lieven J; Fardon, Thomas C; Wilson, Robert; Loebinger, Michael R; Skrbic, Dusan; Obradovic, Dusanka; et al.
Summary: Background: Patients with bronchiectasis often have concurrent comorbidities, but the nature, prevalence, and impact of these comorbidities on disease severity and outcome are poorly understood. We aimed to investigate comorbidities in patients with bronchiectasis and establish their prognostic value on disease severity and mortality rate. Methods: An international multicentre cohort analysis of outpatients with bronchiectasis from four European centres followed up for 5 years was done for score derivation. Eligible patients were those with bronchiectasis confirmed by high-resolution CT and a compatible clinical history. Comorbidity diagnoses were based on standardised definitions and were obtained from full review of paper and electronic medical records, prescriptions, and investigator definitions. Weibull parametric survival analysis was used to model the prediction of the 5 year mortality rate to construct the Bronchiectasis Aetiology Comorbidity Index (BACI). We tested the BACI as a predictor of outcomes and explored whether the BACI added further prognostic information when used alongside the Bronchiectasis Severity Index (BSI). The BACI was validated in two independent international cohorts from the UK and Serbia. Findings: Between June 1, 2006, and Nov 22, 2013, 1340 patients with bronchiectasis were screened and 986 patients were analysed. Patients had a median of four comorbidities (IQR 2–6; range 0–20). 13 comorbidities independently predicting mortality rate were integrated into the BACI. The overall hazard ratio for death conferred by a one-point increase in the BACI was 1·18 (95% CI 1·14–1·23; p<0·0001). The BACI predicted 5 year mortality rate, hospital admissions, exacerbations, and health-related quality of life across all BSI risk strata (p<0·0001 for mortality and hospital admissions, p=0·03 for exacerbations, p=0·0008 for quality of life). When used in conjunction with the BSI, the combined model was superior to either model alone (p=0·01 for combined vs BACI; p=0·008 for combined vs BSI). Interpretation: Multimorbidity is frequent in bronchiectasis and can negatively affect survival. The BACI complements the BSI in the assessment and prediction of mortality and disease outcomes in patients with bronchiectasis. Funding: European Bronchiectasis Network (EMBARC).